2015
DOI: 10.1049/el.2015.1266
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polarisation characteristics of power‐line RCS at 76 GHz for helicopter obstacle detection

Abstract: The polarisation characteristics of a high‐voltage power‐line radar cross‐section (RCS) at 76 GHz are experimentally evaluated to improve the detection conditions of the helicopter obstacle detection radar system. Vertical polarisation transmission and reception (V–V) are normally used to detect power lines. In addition to V–V polarisation, horizontal transmission and reception (H–H) polarisation characteristics are measured for the two types of high‐voltage power lines. For V–V polarisation, the measured RCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The polarization characteristic of the high-voltage power line RCS at 76 GHz band have been evaluated based on the experiments [7]. To detect the power lines by the millimeterwave radar, the vertical polarization is commonly employed to detect the power lines.…”
Section: Circular Polarized 76 Ghz Low Power Radarmentioning
confidence: 99%
See 2 more Smart Citations
“…The polarization characteristic of the high-voltage power line RCS at 76 GHz band have been evaluated based on the experiments [7]. To detect the power lines by the millimeterwave radar, the vertical polarization is commonly employed to detect the power lines.…”
Section: Circular Polarized 76 Ghz Low Power Radarmentioning
confidence: 99%
“…Fig. 1 shows the measured RCS characteristics of the typical highvoltage power lines [7]. The several reflection peaks are observed between -20 degrees and 20 degrees.…”
Section: Circular Polarized 76 Ghz Low Power Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, excessive false-warns would occur. In [7,8,12], it is concluded that the significant backscatters of power lines only exist over narrow aspect angles near the normal incidence at Bragg directions, and this unique Bragg phenomenology is regarded as Bragg pattern. Bragg pattern is often employed to detect power lines with a high detection probability in the presence of background clutter.…”
Section: Introductionmentioning
confidence: 99%
“…In the automotive radars, 77 GHz millimeter-wave system exists for many years. In addition to car driving safety [3,4], the 76 GHz radar system is also used in helicopter anti-collision [5], unmanned ground vehicle [6,7], etc. The operation frequency is typically in the 76-77 GHz band for frequency-modulated continuous wave (FMCW) or pulse Doppler operation.…”
Section: Introductionmentioning
confidence: 99%